El Sistema de Protección a Víctimas y Testigos y su Incidencia en los participantes del proceso penal, en las causas tramitadas en la Fiscalía provincial de Chimborazo durante el periodo febrero 2014 a diciembre 2014. - Pérez Carrillo, Tamara Patricia (2016)
This research work is the result of the main concerns of the Ecuadorian State, referring to the rights of victims in criminal proceedings, it gives us a guideline to harmonize academic spaces whose aim is to give attention to the protected legal interests, to propose safeguard physical, psychological and sexual integrity of victims, witnesses and other participants in the criminal process, incorporating legal contributions from a number of authors who share the same theoretical position of victimology also autonomous criteria that give added value to this investigation is exposed then has four chapters considered in the research work. Chapter I, in the first part comprises the reference framework, which proposes the objectives, the importance of research of the important aspects concerning the study of the protection system for victims and witnesses recognized within the national and international human rights. Chapter II, the theoretical framework is founded on the basis of research, here is the development of the topics and subtopics that allows us to understand the detailed study of the protection of victims and witnesses, which analyzes the measures taken by the state to provide comprehensive assistance to protected when they are in danger, plus all the help provided by the system for reintegration and full compensation of victims is detailed. Chapter III, is the scenario that explains the evaluation of methods and techniques used in the research work, which focuses on the contribution of technical and research methods that met the objectives, and the way and proper guidelines to verify hypothesis, through the application of surveys to determine the physical, psychological and sexual involvement of victims who are accepted by the system as protected.